A qualitative research study exploring the impact of Puma’s celebrity endorsement deals on their brand equity, in a South African sportswear industry context. - Di Bartolo, Marianna (The IIE, 2016)
This research study will add value to market research conducted by the sportswear industry because it confirms that the impact of celebrity endorsements on brand equity is positive. It has been said in the research findings that celebrity endorsement adds a unique value to the sportswear brand that will help distinguish it from competitors in the same market. Furthermore, based on preliminary explanatory research and findings using qualitative research methods, the research study shows that a celebrity endorser will be regarded as credible if they are trustworthy, attractive and experts in their own field. For that reason, sportswear brands will be able to use the criteria identified in this research study to help them select, recruit and retain successful celebrity endorsers that will contribute towards brand building and brand equity. Lastly, the findings of the research study will aid the brand building process while also creating a solid foundation for further research. The findings can support brand managers in making decisions about using celebrity endorsement deal more logically and positively with regard to brand equity.
Keywords: Market research; Brand building